Menelusuri Integrasi Teologi Psikologi Dalam Dialog Tuhan Yesus Dengan Perempuan Samaria Suatu Implikasi Untuk Pelayanan Kontemporer - Purba, Margaretha; Wahyuni, Sri (STT KINGDOM BALI, 2025)
The ministry of the Lord Jesus is one of the ministries carried out with love. The Samaritan woman who experienced an encounter with Jesus. Her encounter with the Lord Jesus brought this woman to find a solution to the problems in her life and which had a good impact on her environment. Hopefully this paper can provide enlightenment and lead us to understand and love people in the same situation as this Samaritan woman. The purpose of this study is to emphasize the importance of knowing and studying psychology in pastoral ministry as carried out by the Lord Jesus to the Samaritan Woman. The research method used is a qualitative biblical approach and takes various existing reference sources according to each discussion. The conclusion of this paper is that Jesus' ministry brings a teaching about the nature of the importance of a true teaching. Jesus gave a teaching about the importance of the woman to accept God personally in her life. A change of heart brings a change in behavior Jesus serves with power.